Influence of Organic Manures on Drought Stress at Different Growth Stages of Wheat (Bangladesh Agronomy Journal, 2021)
A pot experiment was conducted in the net house of the Agronomy department, Sher-e-Bangla Agricultural University, Dhaka during the period from November, 2018 to March, 2019 to evaluate the suitable organic source to mitigate the drought stress impact on wheat. The experiment comprised two factors viz. factor A: Three levels of organic manures, i)  O0 = Control (Without organic manure),       ii) O1 = Cowdung (10 t/ha), iii) O2 = Poultry litter (5 t/ha), and factor B:  four levels of drought i) D0 =  Control (without drought), ii) D1 =  Crown root initiation stage (at 20-29 DAS), iii) D2 =  Booting stage (at 45-54 DAS), iv) D3 = Anthesis stage (at 55-64 DAS). The experiment was laid out in a completely randomized design (factorial) with three replications. Organic manure showed positive impact on yield and cowdung (O1) gave the highest grain yield (4.06 g plant-1). This may be attributed to the highest number of effective tillers plant-1 (3.21), spike length (9.53 cm), spikelet spike-1 (17.31), grains spikelet-1 (2.31) and 1000-grain weight (44.61 g) of wheat in this treatment. In respect of drought imposition treatments, grain yield was found higher in control treatment (without imposition of drought) which was statistically similar with drought imposition at booting stage treatment (D2). These two treatments also showed highest number of effective tillers plant-1, spikelets spike-1, grains spike-1 and 1000-grain weight. Regarding the interaction of organic manure and drought, cowdung without drought imposition (O1D0) and cowdung with drought imposition at booting stage (O1D2) were highest yielder among the other interactions which was attributed to higher 1000-seed weight, number of effective tillers plant-1, spikelets spike-1 and grains spike-1. Results revealed that application of organic manure could reduce the impact of drought on wheat irrespective of growth stages. However, application of cowdung (10 t ha-1) was found more effective to combat drought impact at booting stage of wheat compared to other growth stages.Bangladesh Agron. J. 2020, 23(2): 81-86